Factors Related to The Incidence of Anemia in Women of Reproductive Age in West Solor Subdistrict East Flores Regency - Lewar, Vinsensia Waha; Talahatu, Anna Henny; Toy, Sarci Magdalena (Universitas Nusa Cendana, 2023)
Women of childbearing age are the group most susceptible to anemia. The results of the initial data collection on the number of women of childbearing age who experienced anemia at the Ritaebang Health Center were 102 people. The basic cause of anemia is socio-economic factors. Consumption of diverse food depends on family income as a result, people consume more food from gardens. Garden yields are not always good due to unfavorable geographical conditions, so people's food consumption is less diverse and can cause anemia. The purpose of this study was to determine the factors associated with the incidence of anemia in women of childbearing age in the working area of ​​the Ritaebang Health Center, West Solor District, East Flores Regency. This type of research is analytic survey with a case control study design. This research was carried out in the working area of ​​the Ritaebang Health Center, West Solor District, East Flores Regency in May-June 2022. The sample in this research study was 100 people who were divided into 50 case samples and 50 control samples. The sampling technique used is simple random sampling. Data analysis using chi-square test. The results showed that factors associated with anemia is nutritional knowledge (p= 0.000), type of food (p= 0.000), frequency of eating (p= 0.001). The protective factors is the level of education (p=0,000) and factors that are not related to the incidence of anemia are family income (p= 0.124), food expenditure (p= 1,000), non-food expenditure (p= 0.127), nutritional status (p= 0.158) and duration of menstruation (p= 0.413). Health workers are expected to provide counseling at posyandu about the causes, effects and ways to prevent anemia as well as good consumption patterns so as to increase public knowledge, especially adolescents and woman of childbearing age.